2019
DOI: 10.20533/ijds.2040.2570.2019.0187
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Data-Driven Decision Making in a Canadian School District

Abstract: A main objective in educational settings is to build system and school capacity in data driven decisionmaking and evidence-informed practice in support of the development, monitoring, and measuring of initiatives targeted to support student achievement and well-being. In 2016-2017, the Ottawa-Carleton District School Board (OCDSB) implemented an innovative Data Support Model to provide support to senior staff, school administrators and teams of educators: (1) in the exploration/understanding of data reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In nowadays society where ICT are available in our environment, searching for the best data takes us little effort. In any case, it is found that in this process of searching and interpreting information, the institutional help provided to teachers to understand scientific studies has a significant impact on their research literacy (Pagan et al, 2019), as well as the help provided from peers and colleagues, which also seems to have a positive effect when discussing research findings (Means et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In nowadays society where ICT are available in our environment, searching for the best data takes us little effort. In any case, it is found that in this process of searching and interpreting information, the institutional help provided to teachers to understand scientific studies has a significant impact on their research literacy (Pagan et al, 2019), as well as the help provided from peers and colleagues, which also seems to have a positive effect when discussing research findings (Means et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of decisions and interventions implemented within the classroom depend on the validity of the inferences drawn from the data. Unfortunately, data literacy tends to be low among school personnel, contributing to this limited use of data in decision making [8,9]; however, supporting staff understanding of data can increase their data literacy [10]. Data literacy concerns the ability to analyse and interpret data so that it can be used to inform practice.…”
Section: Evidence-based Practice and Data-based Decision-makingmentioning
confidence: 99%
“…Additionally, teachers need training in DBDM [10], including in collecting, interpreting, and using CBM and other progress monitoring tools to provide instruction [46]. Without preservice training or additional support, it is unlikely that DBDM will have a positive impact on instruction.…”
Section: Implications Of the Lack Of Cbm And Dbdm For Inclusive Educa...mentioning
confidence: 99%
“…In addition to these challenges is an observed lack of skills in how to use data management software (e.g., Excel) for more effective practice-related decisions (Villeneuve and Bouchamma 2020), which is why the technological aspect of the decision-making process is so important (Pagan et al 2019). Consequently, addressing school improvement and the skills required for successful pedagogical practices calls for targeted organizational transformations.…”
Section: Review Of the Literature: Data-driven Decision Making In Edumentioning
confidence: 99%